WEB SERIES SEBAGAI KOMUNIKASI PEMASARAN DIGITAL TRAVELOKA - Radja Erland Hamzah (Jurnal Pustaka Komunikasi, 2018)
Web series is a concept of a series of programs released in the medium of the Internet, usually Youtube become the main platform for the producers of the web series. Then in the process of digital promotion, Traveloka optimize the form of web content series with the theme "Expedisi menebus janji" to introduce this products. such as presenting the ease of use traveloka application as an application that must be owned by every audience where the trip can provide ease of purchasing airline tickets, trains, and hotel booking tickets and payments such as internet and some destruction of domestic and foreign tours. Web series has ease in terms of production and budget. In contrast to advertise on television that must invest considerable cost for results that still exist in the awareness phase. Due to television advertising campaigns, advertisers can only assess the impact of an advertising campaign through a survey or Focus Group Discussion. While through digital media, advertisers can more easily measure, evaluate, and evaluate the performance of promotions directly from the audience by viewing viewers, like, and share them.